Proteomic characterization and cytotoxic potential of proteins from Cuscuta (Cuscuta epithymum (L.) crude herbal product against MCF-7 human breast cancer cell line - Umaima Akhtar; Yamna Khurshid; Bishoy El-Aarag; Basir Syed; Ishtiaq A. Khan; Keykavous Parang; Aftab Ahmed (BMC, 2024)
Abstract Background The burden of breast cancer, the second leading cause of death worldwide, is increasing at an alarming rate. Cuscuta, used in traditional medicine for different ailments, including cancer, is known for containing phytochemicals that exhibit anticancer activity; however, the bioactivities of proteins from this plant remain unexplored. This study aimed to screen the cytotoxic potential of proteins from the crude herbal product of Cuscuta epithymum(L.) (CE) harvested from the host plants Alhagi maurorum and Medicago sativa. Methods The proteins from CE were extracted using a salting-out method, followed by fractionation with a gel filtration chromatography column. Gel-free shotgun proteomics was subsequently performed for protein characterization. The viability assay using MTT was applied to deduce the cytotoxic potential of proteins against MCF-7 breast cancer cells, with further exploration of the effect of treatment on the expression of the apoptotic mediator BCL2-associated X protein (BAX) and B-cell lymphoma protein 2 (BCL-2) proteins, using western blotting to strengthen the findings from the in vitro viability assay. Results The crude proteins (CP) of CE were separated into four protein peaks (P1, P2, P3, and P4) by gel filtration chromatography. The evaluation of potency showed a dose-dependent decline in the MCF-7 cell line after CP, P1, P2, and P3 treatment with the respective IC50 values of 33.8, 43.1, 34.5, and 28.6 µg/ml. The percent viability of the cells decreased significantly upon treatment with 50 µg/ml CP, P1, P2, and P3 (P < 0.001). Western-blot analysis revealed upregulation of proapoptotic protein BAX in the cells treated with CP, P3 (P < 0.01), and P2 (P < 0.05); however, the antiapoptotic protein, BCL-2 was downregulated in the cells treated with CP and P3 (P < 0.01), but no significant change was detected in P2 treated cells. The observed cytotoxic effects of proteins in the CP, P1, P2, and P3 from the in vitro viability assay and western blot depicted the bioactivity potential of CE proteins. The database search revealed the identities of functionally important proteins, including nonspecific lipid transfer protein, superoxide dismutase, carboxypeptidase, RNase H domain containing protein, and polyribonucleotide nucleotidyltransferase, which have been previously reported from other plants to exhibit anticancer activity. Conclusion This study indicated the cytotoxic activity of Cuscuta proteins against breast cancer MCF-7 cells and will be utilized for future investigations on the mechanistic effect of active proteins. The survey of CE proteins provided substantial data to encourage further exploration of biological activities exhibited by proteins in Cuscuta.